Pengembangan Lembar Kerja Peserta Didik Berbasis Keterampilan Proses Sains pada Tema Hujan Asam Kelas VII SMP - Khaeriyah Khaeriyah; Dwi Indah Suryani; Annisa Novianti Taufik (UNIB Press, 2022)
The aim of this research was to examine the level validation of student worksheets based on science process skills with the theme of acid rain for class VII SMP. This research was an RnD (Research and development) research using a development model by Thiagarajan which was adapted into 3D (define, design and develop). The data collection instrument used was a questionnaire in the form of an assessment instrument for student worksheets. The assessment of the student worksheets consists of the feasibility of content, the feasibility of presentation, the feasibility of science process skills, the feasibility of language and the feasibility of graphics. The results of the assessment carried out by material expert validators, media expert validators and practitioner expert validators on student worksheets based on science process skills on the theme of acid rain for class VII junior high school, namely 90.27% for content feasibility, 92.7% for presentation feasibility, 90.62% for science process skills feasibility, 88.63% for language feasibility and 84,61 for graphics feasibility. So the percentage of the final score for the assessment of the student worksheets is 88.47% with very valid criteria, it means that the student worksheets is suitable for use in science learning.